Embolização via arterial com injeção de onyx para o tratamento de fístulas arteriovenosas durais nutridas também por ramos das artérias carótidas internas e vertebrais - Abud, Thiago Giansante [UNIFESP] (2017)
Objective: To demonstrate whether arterial embolization with Onyx (Medtronic-Covidien, Irvine, California) injection of dura mater arteriovenous fistulas (RVFDs) partially fed by the meningeal branches of the carotid sphid arteries or branches of the vertebral arteries is safe and effective. Method: 40 FAVDs partially nourished by the tentorial artery, branch of the internal carotid artery (ICA) and / or posterior meningeal artery, branch of the vertebral artery. These FAVDs were embolized with Onyx through the middle meningeal artery or the occipital artery, branches of the carotid artery external. We have reviewed the occurrence of reflux for arteries with carotid or vertebral origin. Results: In all cases, reflux occurred only in the first millimeters of the arterial branches from the internal or vertebral carotid arteries, but slowly enough to be controlled by the interruption of the injection of Onyx. The reflux was always minimal and the Onyx never reached the ostium of these arteries. There were no cerebral ischemic complications in our series.